2008
DOI: 10.1002/ejoc.200700874
|View full text |Cite
|
Sign up to set email alerts
|

Two Straightforward Strategies for the Synthesis of Thiodisaccharides with a Furanose Unit as the Nonreducing End

Abstract: Keywords: Thiodisaccharides / Furanose / Glycosylation / Catalysis / Molybdenum / Michael addition Thiodisaccharides having a 1-thiopentofuranose nonreducing end were synthesized by two routes starting from per-Oacylaldofuranoses with arabino, ribo, and xylo configurations. These glycosyl donors were converted into S-glycosyl isothiourea derivatives as precursors of 1-thiofuranose units, which were generated in situ and trapped by a sugar enone to produce, by Michael addition, the thioglycosidic linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…17 In another approach, the Michael addition of thioaldoses to the α,β-unsaturated systems of sugar enones, successfully produced 3-and 4-deoxythiodisaccharides and other structurally related compounds. [18][19][20][21][22][23][24] Some of the disaccharides obtained proved to be good inhibitors of glycosidases such as the E. coli β-galactosidase 21,24 and others. 25 The ring-opening reaction of epoxides also yielded (13) and (14) thiodisaccharides under stereoselective processes.…”
Section: Introductionmentioning
confidence: 99%
“…17 In another approach, the Michael addition of thioaldoses to the α,β-unsaturated systems of sugar enones, successfully produced 3-and 4-deoxythiodisaccharides and other structurally related compounds. [18][19][20][21][22][23][24] Some of the disaccharides obtained proved to be good inhibitors of glycosidases such as the E. coli β-galactosidase 21,24 and others. 25 The ring-opening reaction of epoxides also yielded (13) and (14) thiodisaccharides under stereoselective processes.…”
Section: Introductionmentioning
confidence: 99%
“…[1] They are particularly useful probes for enzyme inhibition studies. [3][4][5][6][7] The molecular basis of the inhibition of the β-galactosidase from E. coli by selected S-disaccharides has been studied by using a combination of NMR spectroscopy and molecular modelling techniques. [2] In our laboratory, we have synthesized a number of thiodisaccharides that proved to be inhibitors of specific glycosidases.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Varela and co-workers described the use of MoO 2 Cl 2 to promote the thioglycosylation of the thiol group of 6-thiosugars by per-O-acylfuranose yielding a thiodisaccharide with complete 1,2-trans diastereocontrol (Scheme 30). 71 Chen and co-workers have also shown that MoO 2 Cl 2 shows remarkable catalytic activity for the deacylation of esters in methanol. Highly chemoselective processes were achieved for functionalized substrates possessing different ester or ether groups (Scheme 31).…”
Section: Amphoteric Lewis Acid-lewis Base Catalyzed Reactionsmentioning
confidence: 97%